Utilization of Garlic (Allium sativum) as a Functional Supplement to Enhance the Health and Performance of Cultured Fish: A Systematic Literature Review - Permatasari, Sheny (Research and Social Study Institute, 2025)
Background: The increasing demand for aquaculture production requires the use of foods that not only meet nutritional needs but also promote fish health. The use of natural food additives has become an important alternative to reduce dependence on synthetic antibiotics. One of the most extensively studied natural food additives is garlic (Allium sativum). Garlic has been found to eliminate major pathogenic bacteria, strengthen immunity, improve health status, enhance growth, and increase flesh quality in freshwater fish. With its multifunctional properties, garlic represents a promising functional feed additive to enhance growth performance, food utilization, and stress resistance in cultured fish.Aims: This article was prepared using a systematic literature-review approach on the effects of garlic supplementation in aquaculture feeds.Methods: A systematic literature search was conducted for articles published within the last ten years in Scopus‐or SINTA‐indexed journals. The review included: (1) experimental studies investigating the effects of garlic supplementation in fish feed or rearing media; (2) studies involving growth, physiological, immune, or water quality parameters; and (3) articles focusing on aquaculture species such as tilapia (Oreochromis niloticus), common carp (Cyprinus carpio), rohu (Labeo rohita), rainbow trout (Oncorhynchus mykiss), and groupers (Epinephelus spp.).Results: The evidence has been shown that garlic can enhance growth performance, food efficiency, and immune response in fish, particularly in species such as tilapia, carp, rainbow trout, rohu and grouper. The effective dosage generally ranges between 0.5–3% garlic powder in food, with variations depending on species and application methods.Conclusion/ Recommendation: Future studies should focus on developing probiotic–herbal feed products based on fermented garlic and assessing the economic and social feasibility of natural phytobiotic applications in intensive aquaculture systems.